Producción de biopolímero sintetizado por Leuconostoc pseudomesenteroides con propiedades aglomerantes para el control de material particulado en minería - Mendoza Chacón, Manuela (2019)
The purpose of this research was to produce a biopolymer as a sustainable alternative to conventional additives for controlling particulate matter in mining. The production includes the synthesis by fermentation, precipitation, drying and spraying of the biopolymer for its subsequent application in mining soils. The synthesis with Leuconostoc pseudomesenteroides ME17 was done by batch fermentation where production conditions were evaluated in temperature ranges between 25-30 ° C, sucrose concentration between 70-90 g / L and inoculum percentage between 4–10%, obtaining an increased production of biopolymer (11.93 g / L) under conditions of sucrose concentration 70 g / L, inoculum percentage at 4% and temperature of 25 ° C. Ethanol precipitation, drying and spraying were necessary to facilitate application in the soil. By means of the analysis by infrared transmission spectroscopy with Fourier transform (FTIR), functional groups characteristic of polymeric materials and structure similar to dextran obtained with other strains of L. mesenteroides were determined. Through dispersion and resistance tests, the property of the biopolymer to agglomerate and compact soil particles was demonstrated, achieving 100% agglomeration in soil samples with 5% biopolymer and resistance to point loads of up to 1.19 MPa